Evaluation of anti-inflammatory activity of docosahexaenoic acid on carrageenan induced paw oedema in rats - Singhal, Tulika; Chansoria, Arvind; Kothari, Saroj (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Inflammation is a tissue reaction to infection, irritation of foreign substance. It is a part of the host defence mechanism but if in excess it becomes harmful. Docosahexaenoic acid (DHA) is omega-3-derivative of alpha-linolenic acid. This study was conducted to determine the anti-inflammatory activity of DHA and its comparison with standard drug diclofenac. Methods: The study was carried out by using inflammatory models in male albino rats. Rats were divided into 4 groups of 6 animals of each. The anti-inflammatory activity was studied with carrageenan induced rat paw edema. The anti-inflammatory activity of DHA was compared with standard drug diclofenac. The study parameters for acute inflammation was assessment of reduction in inflammation and the percentage inhibition of the paw edema. Results: DHA 200 mg/kg, DHA 300 mg/kg, and diclofenac 10 mg/kg showed 58%, 64%, and 67% reduction in paw volume, respectively. The DHA showed significant (p<0.05) anti-inflammatory activity in both dosages as compared to control and was dose dependent. Conclusions: DHA produced dose dependent anti-inflammatory activity which suggest its probable use in the treatment of inflammation.